4. Change In The Total Abdominal Fat Content Of Broiler Chicken (Gallus Sp.) Gived Non-Commercial Rations Which Fermentation Moringa Leave (Moringa Aloifera Lamk) - Al Azhar; Intan Firdaus; Nuzul Asmilia; M. Isa; Rosmaidar Rosmaidar; Mustafa Sabri (Jurnal Medika Veterinaria, 2019)
The purpose of this research was to determine the effect of fermented Moringa aloifera Lamk Leaf Flour (FMLF) on the amount of abdominal fat content in broiler chickens (Gallus sp). Twenty eight broiler chickens were randomly design into 4 treatment groups with 7 replications each. The (P0) as control group was given 100% commercial ransom, (P1) was given 95% commercial ransom and 5% FMLF, (P2) was given 92.5% and 7.5% FMLF, and (P3) was given 90% commercial ransom and 10% FMLF. The ransom was given for 23 days. The results showed that the abdominal fat contant of broiler chicken in P1 was significantly higher (P0,05) than that of P0, P2 and P3 There was no decrease in fat abdominal contant of broiler chicken in P1, P2 and P3 compared to that in P0 control. In conclusion, subtitusion of commercial ransom with FMLF up to 10% did not result in a decrease of abdominal fat content of broiler chickens.